Impact of surgical wait times on oncologic outcomes in resectable pancreas adenocarcinoma. Issue 6 (June 2020) - Vasilyeva, Elizaveta; Li, Jennifer; Desai, Sameer; Chung, Stephen W.; Scudamore, Charles H.; Segedi, Maja; Kim, Peter TW
Abstract: Background: Timely surgical resection in patients with suspected or diagnosed pancreas adenocarcinoma is an essential part of care. We hypothesized that longer surgical wait time was associated with worse oncologic outcomes. Methods: A retrospective cohort of patients (N = 144) with resectable pancreas adenocarcinoma was divided into four wait time groups (<4, 4–8, 8–12, and >12 weeks), defined from the time of diagnosis on cross-sectional imaging. Overall and recurrence-free survival were analyzed using the Kaplan–Meier method and Cox proportional hazards regression. A higher rate of conversion to palliative bypass in patients waiting over 4 weeks was observed and further analyzed using post-hoc multivariate regression. Results: On multivariable analysis, longer wait time was associated with improved overall (HR 0.49, 95% CI: 0.28–0.85) and recurrence-free survival (HR 0.29, 95% CI: 0.15–0.56) in >12 weeks compared to <4 weeks group. On post-hoc analysis, longer wait time over 8 weeks was positively associated with palliative bypass (OR 5.33, 95% CI: 1.32–27.88). Conclusion: Wait time over 8 weeks was associated with a higher rate of palliative bypass. There was an improvement in overall and recurrence-free survival in patients who waited over 12 weeks, likely due to selection bias.